E-136 Morphology of mycotic aneurysms and outcomes. (23rd July 2022) - Krothapalli, N; Tsikvadze, M; Akram, N; Elmashad, A; Desai, N; Tunguturi, A; Mehta, T; Patel, S
Abstract : Introduction: Mycotic aneurysms or infectious intracranial aneurysms (IIA) are rare and life-threatening cerebrovascular complications of infective endocarditis. As prompt diagnosis and treatment of IIA prior to cardiac valve surgery has been under deliberation, our study aims to analyze data from a single center to characterize the morphology and outcomes of mycotic aneurysms. Methods: We performed a retrospective chart review of all patients ≥18 years who had a diagnosis of infective endocarditis between January 2017 through June 2021. We identified IIAs by retrospective chart review. A descriptive analysis for continuous and categorical variables was performed using SAS 9.4 version. Results: Of 403 patients with infective endocarditis, we identified 18 (4.5%) with mycotic aneurysms. Vegetation size was >10 mm in 8 (44%) patients and Staphylococcus aureus was the typical (56%) etiologic organism. Mitral (44%) and aortic (39%) valves were primarily affected. The mean age of our population was 54 ± 4.7 years, with 8 (44%) female patients. The mean size of IIA was 2.87 mm and average size of treated aneurysm was 5.36 mm. The most common location was at M2 (33%), M4 (17%), A1 (17%), M3 (11%), A3 (11%) and P4 (11%) segments. In our IIA subset, 7 (39%) patients underwent endovascular or surgical treatment to secure aneurysm prior to cardiac valve surgery. One was treated with embolic-particle, 3 with Onyx, 2 with coiling and 1 with surgical resection. Prior to surgery, 14 (78%) patients had acute ischemic stroke with average stroke volume of 9 mL and 10 (56%) patients had hemorrhagic stroke with average volume of 5 mL. The average duration from maximum burden of stroke to surgery was 7 days. Postoperative hemorrhage was observed among 3 patients in the unsecured group, but no further bleeding was noted in the treated IIA group. Regarding outcomes, 11 patients had unsecured IIA and 5 were discharged to home (18%) or rehab (27%) while 6 (55%) patients succumbed to in-hospital death. In comparison, all 7 patients with secured mycotic aneurysms had favorable discharge to home (14%) or rehab (86%). Conclusion: Patients with secured mycotic aneurysms are less likely to have in-hospital mortality from postoperative hemorrhage and more likely to have better outcomes upon discharge. This snapshot study warrants further investigation to determine the optimal safe timing between securing IIAs to valvular surgery. Disclosures: N. Krothapalli: None. M. Tsikvadze: None. N. Akram: None. A. Elmashad: None. N. Desai: None. A. Tunguturi: None. T. Mehta: None. S. Patel: None.